4
$\begingroup$

I am trying to do the following proof: "show that there exists an integer c such that $$c*\ln(2)- \frac{1}{2} \, (\ln(2))^2 = \sum_{n=1}^{\infty} \frac{ (-1)^n \ln(n)}{n}$$

I have thought of replacing log(n) by the Von Mangolt function, without success. I'm also thinking that I might need to use the Chebychev approximations theorem. i.e.
$$ \frac{c_{1} \, x}{\ln(x)} \leq \pi(x) \leq \frac{c_{2} \, x}{\ln(x)}$$

Thoughts, anyone? J.M.

$\endgroup$
1
$\begingroup$

The key point here is to notice that we can get the factors of $\ln n$ in the numerator by differentiating a Dirichlet series. With

$$\eta(s) = \sum_{n = 1}^{\infty} \frac{(-1)^{n-1}}{n^s}$$

for $\operatorname{Re} s > 0$, we have

$$\eta'(s) = \sum_{n = 1}^{\infty} \frac{(-1)^n\ln n}{n^s}\,,$$

so your series is $\eta'(1)$. Using $\eta(s) = \bigl(1 - 2^{1-s}\bigr)\zeta(s)$, immediately for $\operatorname{Re} s > 1$, then by the identity theorem globally, and the Laurent series of $\zeta(s)$ about $1$,

$$\zeta(s) = \frac{1}{s-1} + \gamma - \gamma_1\cdot (s-1) + \dotsc\,,$$

together with

$$1 - 2^{1-s} = 1 - \exp \bigl(-(s-1)\ln 2\bigr) = (\ln 2)(s-1) - \frac{(\ln 2)^2}{2}(s-1)^2 + \dotsc\,,$$

we obtain the Taylor expansion of $\eta(s)$ about $1$:

\begin{align} \eta(s) &= \biggl((\ln 2)(s-1) - \frac{(\ln 2)^2}{2}(s-1)^2 + \dotsc\biggr) \biggl(\frac{1}{s-1} + \gamma + \dotsc\biggr) \\ &= \biggl(\ln 2 - \frac{(\ln 2)^2}{2}(s-1) + \dotsc\biggr) \bigl(1 + \gamma(s-1) + \dotsc\bigr) \\ &= \ln 2 + \biggl(\gamma\ln 2 - \frac{(\ln 2)^2}{2}\biggr)(s-1) + \dotsc\,. \end{align}

Thus we have

$$\eta'(1) = \gamma \ln 2 - \frac{(\ln 2)^2}{2}$$

and the constant $c$ is not an integer, it is the Euler (or Euler–Mascheroni) constant $\gamma \approx 0.5772$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.